Rattlesnake River Adventure B.11 - Thomas, Jerry D.; Nang Chan Yeema (Nampa, ID USA Pacific Press Publishing Association, 2000)
During an otherwise exciting rafting trip with her church school friends, Maria frets over something she overhead her brother say before they left.
Keywords: Story Collection